Association between secondhand smoke exposure in pregnant women and their socioeconomic status and its interaction with age: a cross-sectional study - Wensu Zhou; Xidi Zhu; Zhao Hu; Shaojie Li; Baohua Zheng; Yunhan Yu; Donghua Xie (BMC, 2022)
Abstract Background Existing evidence highlights that exposure to secondhand smoke (SHS) is a risk factor for pregnant women's health and is possibly affected by individual characteristics. This study aimed to explore the effect of individual socioeconomic status (SES) on SHS exposure among pregnant women in the third trimester and the interaction effect of age. Methods A total of 678 nonsmoking pregnant women with a median age of 29.0 years from 14 communities in a medium-sized city were recruited for this survey. Exposure to SHS was defined as the self-reported smoking habit of a spouse/partner. Individual SES characteristics consisted of marital status, educational attainment, employment and per capita monthly income. Results There were 238 (35.1%) participants who suffered from SHS exposure. Compared to the pregnant women who were employed, those who were unemployed were more likely to suffer from SHS exposure (OR = 1.572, 95% CI: 1.013-2.441). Participants who had a high school or technical secondary school education were more likely to be exposed to SHS than those with a college education or above (OR = 1.601, 95% CI: 1.029-2.449). Advanced age was a protective factor for participants with a college education or above (OR = 0.939, 95% CI: 0.884-0.997), but age increased the risk of SHS exposure among women who had unstable marriages (OR = 1.256, 95% CI: 1.019-1.549). Conclusion Exposure to SHS was very common among pregnant women in the third trimester. Pregnant women with a low SES and an older age should be considered a key population for the implementation of public health interventions.